Robustness study of the pounding tuned mass damper for vibration control of subsea jumpers. (30th July 2015) - Li, Hongnan; Zhang, Peng; Song, Gangbing; Patil, Devendra; Mo, Yilung
Abstract: A previous study by the authors proposed a new type of damper, the pounding tuned mass damper (PTMD), which uses the impact of a tuned mass with viscoelastic materials to effectively dissipate vibration energy, for structural vibration control. However, the control performance is unknown if the PTMD is not tuned to the targeted frequency of the primary structure. This paper aims to study the robustness of the PTMD against the detuning effect both numerically and experimentally. The control object was chosen as a subsea jumper, which is a flexible M-shaped pipeline structure commonly used in offshore oil and gas production. In this paper, a 15.2 m (50 feet) long jumper incorporated with a PTMD was set up. To enable the numerical study, the equation of motion of the jumper along with the PTMD was derived. Three testing cases were numerically studied: free vibration, forced vibration and forced vibration with varied frequencies. In all cases, the PTMD can effectively suppress the structural vibration when the natural frequency was off-tuned. Furthermore, experimental studies were conducted. The experimental results also implied the robustness of the proposed PTMD.